Risk perception, road behavior, and pedestrian injury among adolescent students in Kathmandu, Nepal - Poudel‐Tandukar, Kalpana (BMJ Group, 2007)
OBJECTIVE: To examine the relationship between the perceived safety of specified road behaviors, self‐described road behaviors, and pedestrian injury among adolescent students in Kathmandu, Nepal. METHODS: A cross‐sectional study was conducted among 1557 adolescents in grades 6–8 across 14 schools in Kathmandu using a self‐administered questionnaire in 2003. A multiple logistic regression analysis was used to analyze the data. RESULTS: Adolescents were more likely to suffer from pedestrian injury when they did not always “wait for green signals to cross the road”. There were no significant associations between road behaviors such as “looking both ways along the road before crossing” or “playing in the road or sidewalks” and pedestrian injury. Adolescents who “perceived it safe to cross the road from any point” or “did not perceive it to be safer to cross the road at a zebra crossing” were less likely to “look both ways” or “wait for green signals” before crossing the road. Adolescents who “perceived it to be safe to play in the road” were more likely to play in the road or sidewalk. Similarly, this study showed a positive association between road safety education and adolescents' road crossing behaviors. CONCLUSION: Adolescents' road behaviors, except for compliance with green signals, were not significantly associated with pedestrian injury. This suggests that a behavioral approach without modification of the traffic environment (such as provision of crossing signals) might not effectively prevent the occurrence of pedestrian injury in developing countries with poor traffic conditions.